Gekko canaensis sp. nov. (Squamata: Gekkonidae), a new gecko from Southern Vietnam - van Tri, Ngo; Gamble, Tony (Zootaxa, 2011)
A new species of Gekko Laurenti 1768 is described from southern Vietnam. The species is distinguished from its congeners by its moderate size: SVL to maximum 108.5 mm, dorsal pattern of five to seven white vertebral blotches between nape and sacrum and six to seven pairs of short white bars on flanks between limb insertions, 1–4 internasals, 30–32 ventral scale rows between weak ventrolateral folds, 14–18 precloacal pores in males, 10–14 longitudinal rows of smooth dorsal tubercles, 14–16 broad lamellae beneath digit I of pes, 17–19 broad lamellae beneath digit IV of pes, and a single transverse row of enlarged tubercles along the posterior portion of dorsum of each tail segment.